Asian Archaeology - Shelach, Gideon; Teng, Mingyu; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer.)
Asian Archaeology is an academic English-language journal that publishes original studies based on field archaeological data as well as new theoretical and methodological analyses and synthetic overviews of topics in the field of Asian archaeology, emphasizing the archaeology of China but including neighboring regions of eastern and Southeast Asia as well. The journal$1 (Bs readership is international in nature, including scholars from China, Europe, Australia the USA and Asia. Through overcoming the language barrier toward access to the archaeology of eastern Asia, it aims to become a central international forum for the study of Asian archaeology. We hope that the journal will contribute not only to a better understanding of the history and cultures of Asia, but also to the development of a global approach to archaeology.s
Keywords: Archaeology; Archaeology